Forms of Directive Illocutionary Acts in Steve TV Show: A Pragmatic Analysis - Aritonang, Roby Octo; Ambalegin ambalegin (eScience Humanity Journal, 2023)
Language analysis involves examining various aspects of a language, such as its structure, meaning, and usage, to understand how it works and how people use it to communicate. The purpose of this research aimed to ascertain the acts and forms of directive acts on “Steve TV Show” YouTube Channel. The data were analyzed by using Searle (1979) directive acts theory and forms of directive acts Theorized by Kreidler (1998). This descriptive qualitative research used an observational and non- participatory technique. The researcher gathered data by viewing the episodes and that the researcher did not participate in the show. This research employed the pragmatic identity method and the pragmatic competence-in-equalizing technique to analyze the data. This research discovered three forms of directive acts: declarative, imperative, and interrogative. The acts are request, ask, tell, command, order, and suggest. The form of interrogative mostly found because the Talk Show telling about Interview a guest.